2015
DOI: 10.5966/sctm.2014-0264
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage Repair Using Composites of Human Umbilical Cord Blood-Derived Mesenchymal Stem Cells and Hyaluronic Acid Hydrogel in a Minipig Model

Abstract: The cartilage regeneration potential of human umbilical cord blood-derived mesenchymal stem cells (hUCB-MSCs) with a hyaluronic acid (HA) hydrogel composite has shown remarkable results in rat and rabbit models. The purpose of the present study was to confirm the consistent regenerative potential in a pig model using three different cell lines. A full-thickness chondral injury was intentionally created in the trochlear groove of each knee in 6 minipigs. Three weeks later, an osteochondral defect, 5 mm wide by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(64 citation statements)
references
References 50 publications
2
62
0
Order By: Relevance
“…21 Chitosan is structurally analogous to GAGs, and HA is a major component of the ECM in the NP. 10,12,14 Hydroxyl groups in HA can cross-link with amino groups in CS. CS when combined with glycerol phosphate and HA can undergo a sol-gel transition at 37°C by covalent crosslinking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Chitosan is structurally analogous to GAGs, and HA is a major component of the ECM in the NP. 10,12,14 Hydroxyl groups in HA can cross-link with amino groups in CS. CS when combined with glycerol phosphate and HA can undergo a sol-gel transition at 37°C by covalent crosslinking.…”
Section: Discussionmentioning
confidence: 99%
“…HA has been used broadly for osteoarthritis treatment, 11 as an intra-articular injective material, and has been proven to support cell proliferation and maintain the chondrogenic phenotype. 12 It has been demonstrated that HA-based hydrogels can direct recovery or replacement of the endogenous NP for NP tissue engineering and cellular therapies. 13 Another suitable candidate for cartilage and NP tissue repair is chitosan.…”
Section: Introductionmentioning
confidence: 99%
“…Jung showed that enhancement of cartilage repair with the use of collagen type I/III membrane significantly improves the repair tissue quality in minipigs [37]. In addition, use of allogenic MSC and xenoimplantation of human umbilical cord bloodderived MSC were tested in this animal model, showing induction of cartilage healing by those cell types [42,44]. Efficacy of MSC/scaffold constructs have been shown in other large animals such as sheep, horse, and goats [45][46][47][48][49].…”
Section: Large Animal Studiesmentioning
confidence: 99%
“…Among those, a (mini)pig model has been most frequently employed in previous studies [37][38][39][40][41][42][43][44]. Various cell types and materials were tested in the studies.…”
Section: Large Animal Studiesmentioning
confidence: 99%
See 1 more Smart Citation